Some Aspects of Modeling in the Study of COVID-19 Data - Mustafa, Syed Khalid; Lyashenko, V.; Ahamad, N. Ameer; Ajmal, Mohammad Rehan; Ahmad, M. Ayaz (International Journal of Pharmaceutical Research, 2021)
Human society or civilization is constantly faced with various tests. One such test is the COVID-19 pandemic, which is associated with the spread of a special type of coronavirus. Therefore, humanity is forced to find adequate measures to protect against the COVID-19 pandemic. For this purpose it is needed to know the reliable statistics. Additionally, it is important to know the features of the spread of COVID -19, to be able to make effective forecasts. This can be possible only by using various models. Different models take into account with specific features for the future prediction of the spread of the pandemic. These basic aspects are discussed in this work, which helps people for making better decisions for future strategies.
Keywords: Modeling; COVID-19